On the interplay between microstructure, residual stress and fracture toughness of (Hf-Nb-Ta-Zr)C multi-metal carbide hard coatings - Hariprasad Gopalan; Amalraj Marshal; Marcus Hans; Daniel Primetzhofer; Niels Cautaerts; Benjamin Breitbach; Bernhard Völker; Christoph Kirchlechner; Jochen M. Schneider; Gerhard Dehm (Materials & Design, 2022)
The development of sputtered coatings with improved hardness-toughness property combination is widely sought after. Multi-element ceramic carbide (Hf-Nb-Ta-Zr)C coatings with excess carbon, synthesized by DC co-sputtering is presented in this study as a promising candidate to achieve this objective. The specific roles of microstructure and residual stress are decoupled in order to understand their influence on the mechanical properties. Extensive mechanical characterization through in situ testing of focused ion beam fabricated microcantilevers and nanoindentation based approaches are adopted to quantitatively separate the effect of residual stresses on the fracture toughness of the (Hf-Nb-Ta-Zr)C coatings. Residual stress free, microcantilever testing in notched and unnotched conditions, in combination with microstructural characterization unambiguously reveals the intrinsic mechanical behavior of coatings, which solely depend on the microstructure. On the other hand, nanoindentation based testing techniques probe the influence of residual stress and microstructure on the measured mechanical properties. The segregation and thickening of carbon-rich clusters, especially to the grain boundaries with increasing deposition temperatures is speculated to lead to substantial degradation in all mechanical properties measured. An easier fracture path through grain boundaries leads to a reduction in fracture resistance, which is possibly related to carbon enrichment.